2004
DOI: 10.1177/0954008304044121
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Resistance of Polyhedral Oligomeric Silsesquioxane Polyimide to Atomic-Oxygen Attack

Abstract: Hybrid inorganic/organic polymers have been prepared by copolymerizing a polyimide having the same chemical repeat unit as Kapton with an open-cage polyhedral oligomeric silsesquioxane (POSS). These POSS/polyimide hybrid polymers are Kapton-like polymers containing POSS nanoparticles that are chemically bound into the polymer chain. Samples of these POSS polyimides, as well as polyimide controls, have been exposed to a hyperthermal 0-atom beam that is produced by a laser-detonation source. Exposed and unexpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 106 publications
(152 citation statements)
references
References 13 publications
8
142
0
2
Order By: Relevance
“…[29] For various exposures, the step heights (or etch depths) of POSS-PI films were plotted as a function of the step height of the Kapton H ® film. [23] The derivative functions indicated that the 3.5 and 7.0 wt % Si 8 This paper is declared a work of the U.S. Government and is not subject to copyright protection in the United States and increased in depth to 1.4 µm after the second exposure. The top of the SiO 2 -coated Kapton HN ® image was exposed to AO and only had erosion in the scratched area with unaffected neighboring silica-coated Kapton HN ® , demonstrating the effects of damage to silica coatings on Kapton ® .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[29] For various exposures, the step heights (or etch depths) of POSS-PI films were plotted as a function of the step height of the Kapton H ® film. [23] The derivative functions indicated that the 3.5 and 7.0 wt % Si 8 This paper is declared a work of the U.S. Government and is not subject to copyright protection in the United States and increased in depth to 1.4 µm after the second exposure. The top of the SiO 2 -coated Kapton HN ® image was exposed to AO and only had erosion in the scratched area with unaffected neighboring silica-coated Kapton HN ® , demonstrating the effects of damage to silica coatings on Kapton ® .…”
Section: Resultsmentioning
confidence: 99%
“…The beam was produced by the laser detonation source previously described. [9,23] Three samples of each type were exposed to 100k DISTRIBUTION A. Approved for public release; distribution unlimited.…”
Section: Ao Exposure Of Poss-polyimidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface layer of 10 and 20 wt% POSS-Polyimide film has been characterized using XPS before and after incremental exposures to the hyperthermal O-atom source. [19] Details of this study were described by Minton et al [14] XPS survey spectra of C(1s) and Si(2p) peaks were obtained from 0, 10, and 20 wt% POSS-polyimide surface before and after AO exposures, and the Si(2p) spectra are shown in Figure 4. Following exposure of 20wt% POSS polyimide to 100 kpulses of the O-atom beam, the Si(2p) peak shifted from a binding energy of 102.3 eV corresponding to the silsesquioxane (Si 2 O 3 ) to 104 eV approximately corresponding to the formation of SiO 2 .…”
Section: Xps Analysis After Exposure To An Atomic Oxygen Sourcementioning
confidence: 99%
“…[14] The average of 30 step height of the etched and unetched portions was determined by surface profilometry. These measurements were obtained with the use of a Dektak 3 (Veeco Metrology Group, Santa Barbara, CA) surface profilometer.…”
Section: Surface Characterization Of Poss Polyimidesmentioning
confidence: 99%